2019
DOI: 10.4194/1303-2712-v19_5_09
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The quality of Artemia cysts size can be determined by biometrical characterization. In this study, the combined effects of salinity and ferric citrate were studied on the biometric characterization of Artemia by single clonal reproduction under the laboratory condition. Results of control treatment showed increasing of the salinity correlates non-significant with diameter of decapsulated cyst and negatively correlates with the size of untreated cyst and chorion thickness. The effect of low concentrations of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In this work, we provide evidence on the significant effect of salinity and iron concentration on the chorion thickness in two A. franciscana populations. Our results coincide with Wang et al (2019) , given that they found that increased salinity had a negative effect on the chorion thickness. Moreover, since these authors reported that variation in iron concentration also had an effect on the chorion thickness, which was thinner at 5 mg of Fe 2+ /L and thicker at higher iron concentrations, our result also concurs with these findings.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this work, we provide evidence on the significant effect of salinity and iron concentration on the chorion thickness in two A. franciscana populations. Our results coincide with Wang et al (2019) , given that they found that increased salinity had a negative effect on the chorion thickness. Moreover, since these authors reported that variation in iron concentration also had an effect on the chorion thickness, which was thinner at 5 mg of Fe 2+ /L and thicker at higher iron concentrations, our result also concurs with these findings.…”
Section: Discussionsupporting
confidence: 90%
“…This result is not rare given that available data in Artemia indicate that there is wide interpopulation variation in the chorion thickness ( Sorgeloos et al, 1986 ). There is little information on factors that affect the chorion thickness in Artemia ( Wang et al, 2019 ). In this work, we provide evidence on the significant effect of salinity and iron concentration on the chorion thickness in two A. franciscana populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations